Disaster Management in Tourism: Public-Private Collaboration and Early Warning Innovations in Bali and Yogyakarta - Devi Roza Krisnandhi Kausar; Agustan (Universitas Udayana, 2025)
This paper examines the collaborative roles of the public and private sectors in tourism disaster management, with a focus on Bali and Yogyakarta, Indonesia. These regions, renowned for their tourism significance, are highly vulnerable to natural disasters such as volcanic eruptions and earthquakes. Employing a multiple-case study approach, the research utilized semi-structured interviews with tourism stakeholders and focus group discussions with experts. The findings reveal notable differences in disaster preparedness between Bali and Yogyakarta, shaped by variations in policies, industry structures, and resource capacities. Drawing on Collaborative Governance Theory, the study underscores the critical role of structured stakeholder engagement in fostering shared goals, resource pooling, and mutual accountability in disaster management. Additionally, the research highlights the potential of integrating Indonesia’s early warning technologies—such as the Multi-Hazard Early Warning System (MHEWS), tsunami and weather alerts by BMKG, and volcano hazard warnings by PVMBG—into localized disaster management frameworks to enhance preparedness and response. Public-private collaborations at both national and regional levels emerge as pivotal for strengthening disaster resilience in tourism-dependent areas. By aligning collaborative efforts with technological advancements, this study offers actionable insights for improving disaster management practices, safeguarding the tourism industry, and ensuring the well-being of affected communities. The research underscores the importance of comprehensive guidelines, enhanced stakeholder coordination, and the adoption of innovative technologies to mitigate disaster risks and promote sustainable tourism.